2002
DOI: 10.1111/j.1751-0813.2002.tb10817.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of timing of administration of oestradiol benzoate on characteristics of oestrus, timing of ovulation and fertility in Bos indicus heifers synchronised with a progesterone releasing intravaginal insert

Abstract: Administration of ODB at the time of removal of inserts can shorten the time interval to oestrus and ovulation and can reduce fertility when insemination is carried out once daily. Further work is needed to determine if prolonged suppression of follicular development, anovulatory oestrus and premature ovulation occuring in some heifers is associated with administration of ODB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
3
11
0
6
Order By: Relevance
“…Administration of ODB in the presence of ovarian follicles <10 mm in diameter has been associated with anovulatory oestrus in some cows and reduced concentrations of progesterone post ovulation. 22,23 Use of GnRH in dairy heifers has been associated with shorter interoestrus intervals and reduced pregnancy rates following a timed insemination compared with insemination following spontaneous oestrus. 24 Other authors have reported a reduction in plasma concentrations of progesterone in cattle during the luteal phase following ovulation induced with a GnRH agonist compared to spontaneously occurring oestrus.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of ODB in the presence of ovarian follicles <10 mm in diameter has been associated with anovulatory oestrus in some cows and reduced concentrations of progesterone post ovulation. 22,23 Use of GnRH in dairy heifers has been associated with shorter interoestrus intervals and reduced pregnancy rates following a timed insemination compared with insemination following spontaneous oestrus. 24 Other authors have reported a reduction in plasma concentrations of progesterone in cattle during the luteal phase following ovulation induced with a GnRH agonist compared to spontaneously occurring oestrus.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted in mm) that were induced to ovulate following induction of oestrus and ovulation with ODB. 12,19 Similar effects of follicle diameter have also been demonstrated in cattle induced to ovulate with GnRH 11 or LH. 20 In anoestrous beef cows treated with an intravaginal progesterone releasing device and OBD administered at the time of follicle emergence or dominance, concentrations of progesterone in plasma and the average area of corpora lutea were greater in cows that ovulated a mature dominant follicle (13.8 ± 0.4 mm) compared to cows that ovulated a young dominant follicle (9.0 ± 0.6 mm).…”
Section: Discussionmentioning
confidence: 54%
“…11 Also, if ovulation of immature potential preovulatory follicles is attempted then sometimes ovulation does not occur and if oestrogen is used as the ovulatory induction agent then anovulatory oestrus may ensue. 12,13 The advantages of inducing ovulation however, include improving reproductive performance in animals that may be anoestrous at the time of treatment, improving submission rates to AI and increasing the precision in the timing of onset of oestrus. [14][15][16] The aim of this study was to re-examine and compare the reproductive performance and pattern of onset of oestrus in heifers in which oestrous cycles were synchronised with two doses of PGF 2α and oestrus was synchronised with ODB.…”
Section: Resultsmentioning
confidence: 99%
“…2007). Previous studies have shown that the diameter of the pre‐ovulatory follicle can affect the concentrations of progesterone following ovulation, and whether follicles can be competent or not to ovulate (Cavalieri et al. 2002; Wiltbank et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2003) reported that by using a treatment with progesterone for 9 days, the dominant follicle diameter observed in cows at device removal was larger (13.2 mm) than that observed in cows treated for 7 days (11.8 mm). The timing of emergence of potential pre‐ovulatory follicles relative to the time of device removal can affect the diameter of the ovulatory follicle (Cavalieri et al. 2002, 2004; Utt et al.…”
Section: Discussionmentioning
confidence: 99%